Malleable Masculinity Rethinking Paul’s Masculinity in Light of Valerius Maximus - Hylen, Susan E. 1968- (2022)
Scholarly appraisals of Paul’s masculinity differ widely. Some conclude that Paul is presented (by himself or another author) as an ideal man. Others argue that Paul rejects dominant norms of manliness or that he offers a countercultural alternative. This article draws on the work of Valerius Maximus, whose writing has been neglected in this conversation, to argue that Roman imperial culture offered a variety of measures of elite masculinity. Scholars often mention control of self and others as norms of manliness, and of these Valerius emphasizes practices of self-control. Even with this knowledge, however, evaluating masculinity requires discernment. An individual’s motivations and circumstances are essential factors in Valerius’s application of the social norms. The article encourages scholars to consider this more complex set of cultural norms in assessing the manliness of Paul or other New Testament figures.